Impact of the COVID-19 pandemic on psychotropic prescribing: a systematic review - Nikolaos Mastellos; Marie line El Asmar; Kanika I Dharmayat; Antonio J Vallejo-Vaz; Ryan Irwin; Swettha Mahesarajah (BMJ Open)
Objectives The global prevalence of mental health disorders has risen significantly since the beginning of the COVID-19 pandemic. The pandemic has additionally caused disruption to mental health services, leading to a shift from in-person to remote service delivery. Given its long-term impact, it has become critical to evaluate whether changes in health delivery during the pandemic have had an effect on prescribing patterns for commonly prescribed psychotropic drugs. This study aims to assess the impact of the COVID-19 pandemic on changes in psychotropic prescribing patterns in adults, as well as differences in prescribing in different healthcare delivery approaches across various geographical contexts.Design and eligibility requirements Systematic review of cohort, interrupted time-series and cross-sectional studies examining prescribing trends for at least one commonly prescribed psychotropic drug during and after COVID-19 in accessing care remotely or face to face between 1 January 2020 and 17 June 2022.Data sources MEDLINE, EMBASE, CINAHL, HMIC and PsycINFO databases were searched in addition to citation chaining of relevant reviews.Extraction and analysis Study screening, data extraction and quality assessment were completed by two independent reviewers. The PECO strategy was used to devise the systematic review and findings were synthesised narratively.Results 16 studies were eligible for inclusion. Studies documenting changes in psychotropic prescribing trends provided very conflicting findings. There were no stark differences in prescribing outcomes between different healthcare delivery methods (ie, face-to-face consultations vs remote consultations). A noteworthy finding was that the prescribing rate of benzodiazepines was higher in women than men. No particular trends were observed for the prescription rates of hypnotics, antidepressants or antipsychotics.Conclusions Findings support mixed trends in the prescription of psychotropic medications in a range of settings, hindering conclusive statements on COVID-19’s impact on prescribing. In areas where remote consultations are in use, more comprehensive research is required to assess the safety of prescribing in these settings to inform public health policy and assess if the observed trends in our systematic review persist over time (given the increased consideration of remote and telehealth care in delivering services), particularly the safe and effective deployment of these services.